SEKOLAH DARING DAN KETERGANTUNGAN TELEPON GENGGAM PADA REMAJA - Nurul Retno Nurwulan (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Adolescents engage in smartphones cognitively and emotionally. More evidence suggests that they tend to be dependent on and addicted to smartphones. However, smartphone usage is inevitable during the COVID-19 pandemic since students need to attend online class. Previous studies have developed measurement method to evaluate smartphone addiction. This study evaluated 13 to 15-year-old adolescents’ self-awareness of smartphone addiction using problematic use of mobile phones (PUMP) approach. Group discussions were conducted with adolescents who did self-assessment using the problematic use of mobile phones scale. The main findings of group discussions include drivers of excessive smartphone use, smartphone usage behavior when they are with family or friends, barriers to healthier smartphone use, and nighttime habits. Despite its advantages during the COVID-19 pandemic, parents need to supervise and to encourage their children to use smartphones wisely.